Assessing Site Management Practices in the Planning of a Market Building: A Case Study Based on Indonesian Green Building Regulations - Padma Devia, Yatnanta; Ozariyadi, Laurin Atika; Anggraini, Retno (Journal of Novel Engineering Science and Technology, 2025)
Government infrastructure development plays a vital role in improving quality of life and supporting national development goals. In recent years, sustainable development principles, particularly those related to green building practices, have become increasingly relevant. However, these principles remain underutilized in certain public facilities, such as traditional markets. One critical yet often overlooked component is site management, which significantly affects environmental performance from the early planning stage. This study aims to develop a green building assessment framework specifically focused on site management in market building planning. Employing a qualitative descriptive research method with an applied approach, the study uses a case study of a market building in Indonesia, evaluated using site management criteria derived from Indonesian Green Building regulations. To ensure credibility, the framework and assessment are validated through expert judgment from professionals in green building and sustainable site planning. The results reveal that parking lot provision, site processing and accessibility, and private green open space planning are the most influential sub-parameters, contributing to the highest scores in the site management category. The case study building achieved a score of 23 out of 38, indicating a moderate level of compliance. However, deficiencies were identified in sub-parameters such as green open spaces and the lack of Electric Vehicle Charging Station (EVCS) facilities. This study contributes to the field by proposing a targeted, site-specific assessment framework for market buildings, a building typology that is rarely examined in green building literature. Integrating site management early in the design process can improve sustainability outcomes by enhancing public space quality and environmental awareness in urban communities.